KEEFEKTIFAN KALIMAT DALAM TEKS EKSPOSISI SISWA KELAS VIII SMP NEGERI 1 PADANG PANJANG - Astuti, Diana; Pramesti, Utami Dewi (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT This article reveals effective sentences in the exposition text of class VIII students of SMP Negeri 1 Padang Panjang. The purpose of this study is three. First, describe the effectiveness of the sentence in the exposition text of class VIII students of SMP Negeri 1 Padang Panjang in terms of the accuracy of sentence structure. Second, describe the effectiveness of the sentence in the exposition text of class VIII students of SMP Negeri 1 Padang Panjang in terms of the accuracy of word choice. Third, describe the effectiveness of sentences in the exposition text of class VIII students of SMP Negeri 1 Padang Panjang in terms of spelling accuracy. This type of research is a qualitative descriptive method. The source of this research data is the task of students in writing exposition text class VIII Padang Panjang Middle School 1 which was registered in 2018/2019. The sample in this study was determined by proportional random sampling, which is 30 students' work. The results of the study are three. First, the effectiveness in terms of sentence structure is 344 effective sentences and 121 sentences are not effective. Second, the effectiveness of sentences in terms of word choices have 21 effective sentences and 444 sentences not effective. Third, the effectiveness of the sentence in terms of spelling found 253 effective sentences and 212 sentences were not effective. Based on the results of the study it was concluded that of the 465 sentences studied there were 81 effective sentences and 370 sentences not effective. Kata kunci:Kalimat Efektif, Teks Eksposisi